Assessment of the resilience in SEPLS (Socio-Ecological Production Landscapes and Seascapes) in Yanuo Village, Xishuangbanna, Southwest China - Yang, Yunhui; Bai, Keyu; Li, Guanhua; Jarvis, Devra I.; Long, Chunlin (MDPI, 2020)
Participatory ‘assessment workshops’ were held in 2018 in Yanuo Village, Xishuangbanna, Southwest China. The ‘Indicators of Resilience in Socio-Ecological Production Landscapes and Seascapes (SEPLS)’ tool was used to provide the community with a framework for discussion and analysis of socio-ecological processes essential for resilience. Workshops were planned and implemented by local people together with researchers from outside the community. Discussion, including a scoring process, was undertaken using a subset of twenty indicators designed to capture the communities’ perceptions of factors affecting the resilience of their landscapes. The indicators were also used to provide the local community with a framework to discuss both current conditions of resilience and potential areas for improvement. A key result was that the existing community management approach did not include loss of traditional knowledge as a factor that would impact on the livelihoods and well-being of the community. A mechanism to encourage young people to inherit and actively use traditional knowledge was agreed to be necessary and included in economic activities. In addition, the socio-economic infrastructure in the community needs further improvement. This community management assessment framework in Yanuo Village can be scaled out to other communities in tropical montane regions with similar socio-economic environments by supporting stakeholders (policymakers, NGOs and development agencies, etc.).